Construction and application of the emergency resilience capability evaluation scale and model for grassroots medical workers: a cross-sectional study in Guangzhou, China - Wu, Qiaohui; Wu, Linjian; Liang, Xueqing; Xu, Jun; Liu, Li; Huang, Zhijie; Ma, Zhen (Frontiers in Public Health, 2024)
Currently, research on the emergency response capability of medical personnel focused on their mastery of medical professional knowledge, and the establishment of emergency response capability evaluation systems frequently involved the simple use of highly subjective expert consultation methods. No research had been conducted to scientifically and systematically establish a set of emergency resilience assessment systems applicable to grassroots medical personnel from the perspective of assessing medical professional knowledge that medical personnel are obligated to master, nor had any research been conducted to establish a set of emergency resilience assessment models combining attribute hierarchical analysis and gray correlation Not applicable. Clinical trial registration Not applicable.Data are available on reasonable request. The datasets analysed during the current study are available from the corresponding author on reasonable request. Reflexivity statement: The authors include three females and four males and span multiple levels of seniority. While four of the authors specialize in health policy management, the second is a data analysis researcher, and the third and sixth are doctors from different medical authorities. All authors have extensive experience conducting public health researches and policy studies. Ethical Approval Not applicable. This study which is an investigation among normal people, have not involved in ethical issue.The study was performed in accordance with the Declaration of Helsinki. According to the relevant guidelines and regulations published by the government in China (https://www.gov.cn/zhengce/zhengceku/2023-02/28/content_5743658.htm), the need for ethics approval on this research is deemed unnecessary. Informed consent was obtained from all participants. An anonymous questionnaire was used, in which the name, address and other personal information of the participants were not needed.